Improving the thermal efficiency of fin-tube heat exchangers by optimizing geometric parameters of curved rectangular winglet vortex generators - Dan Mugisidi; Oktarina Heriyani; Amir Khalid; Ahmed Rahmani (Mechanical Engineering for Society and Industry, 2026)
Thermal efficiency is a fundamental criterion in the design and operation of heat exchangers because it provides a clear view of the thermal behaviour and reliability of the system. Integrating vortex generators (VGs) with heat exchangers often increases turbulence and enhances the heat transfer rate but at the cost of increased pressure drops. This study aims to maximise the thermal enhancement factor (TEF) in fin–tube heat exchangers by optimising the radial distance, hole width and angular position of curved rectangular winglet vortex generators (CRW-VGs). Computational fluid dynamics analysis is utilised to investigate how variations in radial distance and hole width influence CRW-VG performance. Parameters such as TEF, Nusselt number ratio, friction factor ratio and flow regime were examined. The results show that smaller radial distances suppress mixing vortices and enhance TEF, while larger hole widths generate strong jet flows and increase heat transfer rates. The highest TEF of 1.075 is achieved at an angular position of 120°, a hole width of 0.5 H and a radial distance of 1.25. The study reveals that optimising the geometric parameters of VGs is proven satisfactory for enhancing heat transfer performance and minimising pressure drop.